Predicted equations for ventilatory function among Kuching (Sarawak, Malaysia) population - Djojodibroto, R. Darmanto; Pratibha, G.; Kamaluddin, Bakar; Manjit, S.S; Sumitabha, G; Deva Kumar, A; Hashami, B (Malaysian Medical Association, 2009)
Spirometry data of 869 individuals (males and females) between the ages of 10 to 60 years were analyzed. The analysis yielded the following conclusions: 1. The pattern of Forced Vital Capacity (FVC) and Forced Expiratory Volume in One Second (FEV1) for the selected subgroups seems to be gender dependant: in males, the highest values were seen in the Chinese, followed by the Malay, and then the Dayak; in females, the highest values were seen in the Chinese, followed by the Dayak, and then the Malay. 2. Smoking that did not produce respiratory symptom was not associated with a decline in lung function, in fact we noted higher values in smokers as compared to nonsmokers. 3. Prediction formulae (54 in total) are worked out for FVC & FEV1 for the respective gender and each of the selected subgroups.